A case report of vibration-induced hand comorbidities in a postwoman - Violante Francesco S; Acquafresca Luciano; Barbieri Giuseppe; Bernardelli Sandra; Bonfiglioli Roberta; Graziosi Francesca; Mattioli Stefano; Farioli Andrea; Hagberg Mats (BMC Musculoskeletal Disorders, 2011)
Abstract Background Prolonged exposure to hand-transmitted vibration is associated with an increased occurrence of symptoms and signs of disorders in the vascular, neurological and osteoarticular systems of the upper limbs. However, the available epidemiological evidence is derived from studies on high vibration levels caused by vibratory tools, whereas little is known about possible upper limb disorders caused by chronic exposure to low vibration levels emitted by fixed sources. Case presentation We present the case of a postwoman who delivered mail for 15 years using a low-powered motorcycle. The woman was in good health until 2002, when she was diagnosed with bilateral Raynaud's phenomenon. In March 2003 a bilateral carpal tunnel syndrome was electromyographically diagnosed; surgical treatment was ineffective. Further examinations in 2005 highlighted the presence of chronic tendonitis (right middle finger flexor). Risk assessment From 1987, for 15 years, our patient rode her motorcycle for 4 h/day, carrying a load of 20-30 kg. For about a quarter of the time she drove over country roads. Using the information collected about the tasks carried out every day by the postwoman and some measurements performed on both handles of the motorcycle, as well as on both iron parts of the handlebars, we reconstructed the woman's previous exposure to hand-arm vibration. 8-hour energy-equivalent frequency weighted acceleration was about 2.4 m/s2. The lifetime dose was 1.5 × 109(m2/s4)hd. Conclusions The particular set of comorbidities presented by our patient suggests a common pathophysiological basis for all the diseases. Considering the level of exposure to vibrations and the lack of specific knowledge on the effects of vibration in women, we hypothesize an association between the work exposure and the onset of the diseases.